Ionophore-based potentiometric PVC membrane sensors for determination of phenobarbitone in pharmaceutical formulations - Alrabiah Haitham; Al-Majed Abdulrahman; Abounassif Mohammed; Mostafa Gamal A.E. (Acta Pharmaceutica)
The fabrication and development of two polyvinyl chloride (PVC) membrane sensors for assaying phenobarbitone sodium are described. Sensors 1 and 2 were fabricated utilizing β- or γ-cyclodextrin as ionophore in the presence of tridodecylmethylammonium chloride as a membrane additive, and PVC and dioctyl phthalate as plasticizer. The analytical parameters of both sensors were evaluated according to the IUPAC guidelines. The proposed sensors showed rapid, stable anionic response (-59.1 and -62.0 mV per decade) over a relatively wide phenobarbitone concentration range (5.0 × 10-6-1 × 10-2 and 8 × 10-6-1 × 10-2 mol L-1) in the pH range of 9-11. The limit of detection was 3.5 × 10-6 and 7.0 × 10-6 mol L-1 for sensors 1 and 2, respectively. The fabricated sensors showed high selectivity for phenobarbitone over the investigated foreign species. An average recovery of 2.54 μg mL-1 phenobarbitone sodium was 97.4 and 101.1 %, while the mean relative standard deviation was 3.0 and 2.1 %, for sensors 1 and 2, respectively. The results acquired for determination of phenobarbitone in its dosage forms utilizing the proposed sensors are in good agreement with those obtained by the British Pharmacopoeial method.